ANALISIS STRATEGI PEMUNGUTAN PAJAK BUMI DAN BANGUNAN (PBB) DI KOTA SURABAYA TERHADAP PENINGKATAN REALISASI TARGET PENERIMAANNYA DARI TAHUN 2006-2011 - ANGGRAENI, DIAN (Jurnal Akuntansi AKUNESA, 2012)
The aim of this research is to find out strategy billing tax collection and the earth and government buildings city surabaya to increasing acceptance the realization of the target. In this research using a method of analysis descriptive. Source of data used data is data the primary and secondary. The result showed that the government' s strategy city surabaya currently used not based on to improve the realization of tax revenue target of land and building every year. Keywords: Land and Building tax, Strategy poll, Regional Regulation, The realization of the target